Gendered experiences of social harm in asylum: exploring state responses to persecuted women in Britain, Denmark and Sweden, 2016-2018 - Canning, Victoria (UK Data Service, 2021)
Research undertaken by the Principal Investigator has established that limitations in welfare and psychosocial support can have long term social and emotional implications for women survivors of conflict and persecution, as well as their families, dependents and communities more broadly. Recent upsurges in claims for asylum in Europe, and the increasing need for sustained action from Northern European states, thus places the wellbeing of refugee women as a central concern in this region. This study examines social conditions and support for women seeking asylum in three varying case study politico-economies, namely liberal/neoliberal (Britain), liberal (Denmark) and social democratic (Sweden). It aims to investigate state and organisational responses in these three Northern European states to a) understand socially harmful policy and practice in asylum systems from a gendered perspective and b) develop strategies and recommendations so that such conditions can be mitigated, support improved upon and knowledge shared. Drawing together an intersectional feminist perspective with a social harm framework, this project will address gaps in recognising the micro-level impacts of structural political decisions affecting women seeking asylum. Building on her extensive experience of researching asylum, and utilising connections with governmental and non-governmental organisations in this field, the PI is the ideal candidate to develop research evidence to shape and inform policy and recommendations for best practice in responding to, and supporting, women seeking asylum. Since Hillyard and Tombs first outlined a social harm perspective in 2004, social harm remains empirically, methodologically and theoretically under-developed, particularly in terms of understanding women's experiences of harm. Pemberton (2015) extends the perspective via cross-national quantitative analyses of harm within a politico-economic framework, identifying liberal and neoliberal states as those within which harm is most manifest. However, there remain significant gaps in investigating and understanding the scale, nature and distribution of social harm, not least in terms of the gendered impacts of factors which have can result in physical, psychological, cultural, economic and social harms against women. Although Pemberton's quantitative analysis has drawn social harm research further into the empirical sphere of social sciences, the everyday impacts of structural and political decisions have not yet been explored. An intersectional feminist perspective, which recognises that multiple identities in women's lives can mean multiple oppressions, allows for a timely and nuanced way of examining and addressing the continuum of harms that women seeking asylum can face. This research thus aims to: 1. Address the current shortfalls and gaps in knowledge by expanding empirically generated data pertaining to the micro-level socially harmful impacts resulting from gendered asylum policy with specific reference to physical/mental harms, autonomy harms and relational harms; 2. Situate the experiences of women seeking asylum in the context of nation-specific historical trajectories, and consider ways in which three asylum systems (Britain, Denmark and Sweden) alleviate or exacerbate physical/mental, relational and autonomy harms; 3. Identify what forms of support are available to women seeking asylum, and address ways in which best practice and policy can be disaggregated; 4. Develop policy recommendations for governmental and non-governmental organisations working with women seeking asylum; 5. Create the basis for a novel, sustainable, and long term research agenda around such issues. Three methodologies will be employed: critical analysis of policies and legislation; 15-20 semi-structured practitioner interviews per country with relevant governmental and non-governmental representatives; approximately 3-5 oral histories with women seeking asylum. Research undertaken by the Principal Investigator has established that limitations in welfare and psychosocial support can have long term social and emotional implications for women survivors of conflict and persecution, as well as their families, dependents and communities more broadly. Recent upsurges in claims for asylum in Europe, and the increasing need for sustained action from Northern European states, thus places the wellbeing of refugee women as a central concern in this region. This study examines social conditions and support for women seeking asylum in three varying case study politico-economies, namely liberal/neoliberal (Britain), liberal (Denmark) and social democratic (Sweden). It aims to investigate state and organisational responses in these three Northern European states to a) understand socially harmful policy and practice in asylum systems from a gendered perspective and b) develop strategies and recommendations so that such conditions can be mitigated, support improved upon and knowledge shared. Drawing together an intersectional feminist perspective with a social harm framework, this project will address gaps in recognising the micro-level impacts of structural political decisions affecting women seeking asylum. Building on her extensive experience of researching asylum, and utilising connections with governmental and non-governmental organisations in this field, the PI is the ideal candidate to develop research evidence to shape and inform policy and recommendations for best practice in responding to, and supporting, women seeking asylum. Since Hillyard and Tombs first outlined a social harm perspective in 2004, social harm remains empirically, methodologically and theoretically under-developed, particularly in terms of understanding women's experiences of harm. Pemberton (2015) extends the perspective via cross-national quantitative analyses of harm within a politico-economic framework, identifying liberal and neoliberal states as those within which harm is most manifest. However, there remain significant gaps in investigating and understanding the scale, nature and distribution of social harm, not least in terms of the gendered impacts of factors which have can result in physical, psychological, cultural, economic and social harms against women. Although Pemberton's quantitative analysis has drawn social harm research further into the empirical sphere of social sciences, the everyday impacts of structural and political decisions have not yet been explored. An intersectional feminist perspective, which recognises that multiple identities in women's lives can mean multiple oppressions, allows for a timely and nuanced way of examining and addressing the continuum of harms that women seeking asylum can face. This research thus aims to: 1. Address the current shortfalls and gaps in knowledge by expanding empirically generated data pertaining to the micro-level socially harmful impacts resulting from gendered asylum policy with specific reference to physical/mental harms, autonomy harms and relational harms; 2. Situate the experiences of women seeking asylum in the context of nation-specific historical trajectories, and consider ways in which three asylum systems (Britain, Denmark and Sweden) alleviate or exacerbate physical/mental, relational and autonomy harms; 3. Identify what forms of support are available to women seeking asylum, and address ways in which best practice and policy can be disaggregated; 4. Develop policy recommendations for governmental and non-governmental organisations working with women seeking asylum; 5. Create the basis for a novel, sustainable, and long term research agenda around such issues. Three methodologies will be employed: critical analysis of policies and legislation; 15-20 semi-structured practitioner interviews per country with relevant governmental and non-governmental representatives; approximately 3-5 oral histories with women seeking asylum.